MENUJU SEBUAH TEORI UMUM PEMASARAN - Setyawan, Anton Agus (Benefit: Jurnal Manajemen dan Bisnis, 2012)
This article discusses the urgency of general marketing theory. Marketing becomes avery developed and converged discipline. This is a challenge for marketing scholars to present anew approach in constructing theory. Unfortunately, the dominance of traditional approach inmarketing brings stagnation in the theory construction. Although, general marketing theory isstill a hope for marketing scholars, they should broadened their vision to new approach in theoryconstruction.